Nutritional status of under- five children in a city of Maharashtra: a community based study - Purohit, Laxmikant; Sahu, Priyanka; Godale, Lata B. (International Journal Of Community Medicine And Public Health, 2017)
Background: Children are considered to be the backbone of any nation. Nutritional problems among children cause major morbidity and mortality in India. India is home to the largest number of underweight and stunted children in the world. Aim and objectives: 1) To assess prevalence of underweight, stunting and wasting among under-five children 2) To study factors associated with underweight, stunting and wasting among under-five children Methods: It was community based descriptive cross sectional study conducted during January 2010 to December 2011 at Urban Health Center of the Department of Preventive and Social Medicine catering approximately 27000 populations. 650 under- fives residing in urban field practice area were included in the study with the help of Stratified random sampling technique. Data was analyzed using SPSS software 16 version and OpenEpi Software Version 2.3. Results: 40.46% under five children were stunted, 38.15% were underweight, and 16% were wasted. The difference observed between stunted and normal study subjects with reference to type of family, education of mother, birth weight and birth order were statistically significant. The proportion of under- five children with underweight showed significant association with their age, socioeconomic status, education mother, birth weight and birth order. Proportion of under-five children with SAM and MAM decreased significantly with increase in education status of mother. Significantly higher proportion of under-five children with birth weight less than 2.5 kg and higher birth order were grouped as SAM and MAM. Conclusions: Maternal education, birth weight and birth order of children were significantly associated with all three types of under nutrition i.e. underweight, stunting and wasting. Proportion of children with underweight increases significantly with increase in age and decrease in socioeconomic status. There was no religion wise or gender wise variation in proportion of children with under nutrition was reported among study subjects.